Polyacrylonitrile sodium thiocyanate spinning solution, method for preparing and using the same, and spinning method and polyacrylonitrile precursor

CN116065247BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211337139.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-29
Filing Date
2022-10-28
Publication Date
2026-10-13
Estimated Expiration
2042-10-28

AI Technical Summary

Technical Problem

[0004]目前,聚丙烯腈溶解在硫氰酸钠水溶液,溶解过程容易出现凝胶等现象,导致纺丝溶液中含有凝胶粒子

Benefits of technology

[0024]本发明利用超临界二氧化碳作为介质使聚丙烯腈溶解在硫氰酸钠水溶液中,超临界二氧化碳具有塑化和溶胀作用使得聚丙烯腈分子链段更加舒展,利用其溶胀作用减弱强极性氰基官能团的作用,同时减弱聚丙烯腈大分子链段的缠结作用,提高聚丙烯腈在硫氰酸钠溶液中的溶解度,且采用本发明所述的聚丙烯腈硫氰酸钠纺丝溶液制备聚丙烯腈原丝,推测高固含量的聚丙烯腈原液成型过程可减少断丝现象的发生,有利于成型过程沿纤维轴取向,有利于制备结构均质化致密的聚丙烯腈原丝,提高聚丙烯腈原丝的力学性能和稳定性,由此能够得到质量更加稳定的聚丙烯腈原丝。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003915708940000081
    Figure BDA0003915708940000081
  • Figure BDA0003915708940000082
    Figure BDA0003915708940000082
  • Figure BDA0003915708940000091
    Figure BDA0003915708940000091
Patent Text Reader

Abstract

The present application relates to a kind of polyacrylonitrile sodium thiocyanate spinning solution and its preparation method and application and spinning method and polyacrylonitrile original silk;With the mass fraction, the polyacrylonitrile sodium thiocyanate spinning solution in polyacrylonitrile content is 13.8wt% or more, preferably 14-17wt%, more preferably 14-16wt%. The wet spinning coagulation bath forming process of high solid content polyacrylonitrile original solution of the present application can reduce the occurrence of broken yarn phenomenon, is conducive to the orientation of fiber forming process along fiber axis, is conducive to the preparation of structure homogenization dense polyacrylonitrile original silk, improves the mechanical properties and stability of polyacrylonitrile original silk.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polyacrylonitrile sodium thiocyanate spinning solution, its preparation method and application, as well as a spinning method and polyacrylonitrile precursor fiber. Background Technology

[0002] Carbon fiber (CF) is a new type of high-performance fiber material with a carbon content of over 92% and high strength and modulus. Due to its excellent properties such as high specific strength, high specific modulus, corrosion resistance, fatigue resistance, creep resistance, electrical conductivity, thermal conductivity, and low coefficient of thermal expansion, carbon fiber has a wide range of applications in cutting-edge fields such as aerospace. With the efforts of researchers in various countries, carbon fiber production technology has been continuously developed, and the cost of carbon fiber has been continuously reduced, leading to a continuous expansion of its application range. Currently, carbon fiber is also widely used in wind power, civil aircraft, automobiles, construction, sporting goods, and other fields.

[0003] Polyacrylonitrile (PAN) precursor fibers are an important precursor for the preparation of high-performance carbon fibers. The production process of PAN-based carbon fibers mainly includes the following steps: PAN precursor fiber preparation, precursor fiber pre-oxidation treatment, low-temperature carbonization of pre-oxidized fibers, and high-temperature carbonization treatment. Commonly used polyacrylonitrile spinning solutions include N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, and sodium thiocyanate aqueous solution. The first three are toxic; therefore, some factories use sodium thiocyanate aqueous solution as a solvent in the spinning process.

[0004] Currently, when polyacrylonitrile is dissolved in an aqueous solution of sodium thiocyanate, gelation and other phenomena easily occur during the dissolution process, resulting in gel particles in the spinning solution. Chinese patent CN202110359248.7 prepares a suspension with high solid content during the polymerization process; however, the controllability of the simultaneous polymerization and spinning suspension preparation process in the published patent is unknown, and the filtration of the suspension to remove particles results in a significant waste of material. Summary of the Invention

[0005] The purpose of this invention is to overcome the problems of low solid content and easy gelation during the dissolution process in existing polyacrylonitrile sodium thiocyanate spinning solutions, and to provide a polyacrylonitrile sodium thiocyanate spinning solution and its preparation method, which has the advantage of high solid content.

[0006] To achieve the above objectives, the present invention provides a polyacrylonitrile sodium thiocyanate spinning solution, wherein the polyacrylonitrile content in the polyacrylonitrile sodium thiocyanate spinning solution is 13.8 wt% or more, preferably 14-17 wt%, and more preferably 14-16 wt%.

[0007] Preferably, the number-average molecular weight of the polyacrylonitrile is 20,000 to 100,000.

[0008] Preferably, the polyacrylonitrile sodium thiocyanate spinning solution comprises 40-45 wt% sodium thiocyanate, 14-16 wt% polyacrylonitrile, and 39 wt%-54 wt% water.

[0009] A second aspect of the present invention provides a method for preparing the aforementioned polyacrylonitrile sodium thiocyanate spinning solution, the method comprising:

[0010] Polyacrylonitrile was dispersed in a first aqueous sodium thiocyanate solution to obtain a dispersion slurry. The dispersion slurry was placed in a carbon dioxide atmosphere. Under the carbon dioxide atmosphere, a second aqueous sodium thiocyanate solution was added. Then, CO2 was introduced to pressurize and heat the mixture, so that the CO2 was in a supercritical state for mixing. After mixing, the mixture was cooled and depressurized to obtain a polyacrylonitrile sodium thiocyanate spinning solution.

[0011] A third aspect of the present invention provides the application of the sodium thiocyanate spinning solution of polyacrylonitrile described in the present invention in the preparation of polyacrylonitrile fibers.

[0012] A fourth aspect of the present invention provides a spinning method, the method comprising:

[0013] (1) Prepare a polyacrylonitrile sodium thiocyanate spinning solution according to the preparation method of the polyacrylonitrile sodium thiocyanate spinning solution of the present invention;

[0014] (2) The polyacrylonitrile spinning solution prepared in step (1) is subjected to spinning and hot stretching treatment to obtain polyacrylonitrile precursor fiber;

[0015] In preferred step (2), the spinning method is wet spinning or dry-jet wet spinning; and / or

[0016] The stretching method is thermal stretching, preferably hot water stretching, hot steam stretching, or high-pressure steam stretching; more preferably, the stretching ratio is 2-50 times.

[0017] The fifth aspect of this invention provides a polyacrylonitrile precursor fiber, which is used to test the axial micropore size N times, and obtains the average value L of the N axial micropore size tests as L = (l1 + l2 + l3 + l4 + l5 + ... + l N )*r / N, where r is the radius of the polyacrylonitrile fiber, l N The axial micropore size value of the Nth test; the variance S of the L values ​​of the n polyacrylonitrile precursor fibers. 2 , of which S 2 ≤120, where N is an integer not less than 2 and n is an integer not less than 2.

[0018] Preferably, the tensile strength of the polyacrylonitrile precursor monofilament is 5.5-9 cN / dtex, and more preferably 5.81-8.94 cN / dtex.

[0019] Preferably, the tensile modulus of the polyacrylonitrile precursor monofilament is 95-120 cN / dtex, and more preferably 97.83-115.26 cN / dtex.

[0020] Preferably, the axial micropore size inside the polyacrylonitrile precursor fiber for synchrotron small-angle X-ray scattering testing is 80-1200 nm, more preferably 80-300 nm.

[0021] Preferably, the micropore deviation angle of the polyacrylonitrile precursor monofilament is 10°-30°, more preferably 10°-25°.

[0022] Preferably, the fiber orientation factor of the polyacrylonitrile precursor monofilament is 0.915-0.989, more preferably 0.943-0.989.

[0023] Preferably, the orientation angle of the (100) crystal plane of the polyacrylonitrile precursor monofilament in X-ray diffraction testing is 5°-13°, more preferably 5°-9°.

[0024] This invention utilizes supercritical carbon dioxide as a medium to dissolve polyacrylonitrile in an aqueous sodium thiocyanate solution. Supercritical carbon dioxide has plasticizing and swelling effects, making the polyacrylonitrile molecular chains more extended. This swelling effect weakens the influence of strongly polar cyano functional groups and reduces the entanglement of polyacrylonitrile macromolecular chains, thus increasing the solubility of polyacrylonitrile in the sodium thiocyanate solution. Furthermore, using the polyacrylonitrile-sodium thiocyanate spinning solution described in this invention to prepare polyacrylonitrile precursor fibers, it is speculated that the high solids content of the polyacrylonitrile precursor solution during the forming process can reduce fiber breakage, facilitate orientation along the fiber axis during the forming process, and promote the preparation of homogeneous and dense polyacrylonitrile precursor fibers. This improves the mechanical properties and stability of the polyacrylonitrile precursor fibers, thereby obtaining more stable polyacrylonitrile precursor fibers.

[0025] The preparation method described in this invention utilizes supercritical carbon dioxide assisted treatment to improve the solubility of polyacrylonitrile in sodium thiocyanate solution. This preparation method has advantages such as being environmentally friendly, having controllable mixing, and reducing the use of chemical reagents and sodium thiocyanate solvent. The polyacrylonitrile sodium thiocyanate spinning solution described in this invention has significant industrial application value. Detailed Implementation

[0026] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0027] According to a first aspect of the present invention, the present invention provides a polyacrylonitrile sodium thiocyanate spinning solution, wherein the polyacrylonitrile content in the polyacrylonitrile sodium thiocyanate spinning solution is 13.8 wt% or more, preferably 14-17 wt%, and more preferably 14-16 wt%.

[0028] According to a preferred embodiment of the present invention, the number-average molecular weight of the polyacrylonitrile is 20,000 to 100,000, preferably 20,000 to 80,000.

[0029] According to a preferred embodiment of the present invention, the polyacrylonitrile sodium thiocyanate spinning solution contains 40-45 wt% sodium thiocyanate.

[0030] According to a preferred embodiment of the present invention, the polyacrylonitrile sodium thiocyanate spinning solution comprises 40wt%-45wt% sodium thiocyanate, 14wt%-16wt% polyacrylonitrile and 39wt%-54wt% water.

[0031] All polyacrylonitrile sodium thiocyanate spinning solutions possessing the aforementioned characteristics can achieve the objectives of this invention, and there are no special requirements for their preparation methods. Regarding this invention, according to a second aspect of this invention, this invention provides a method for preparing the aforementioned polyacrylonitrile sodium thiocyanate spinning solution, the method comprising:

[0032] Polyacrylonitrile (PA) is dispersed in a first aqueous sodium thiocyanate solution to obtain a dispersion slurry. The dispersion slurry is then placed in a carbon dioxide atmosphere. Under the carbon dioxide atmosphere, a second aqueous sodium thiocyanate solution is added, followed by pressurization and heating with CO2 to bring the CO2 to a supercritical state for mixing. After mixing, the temperature is lowered and the pressure is released to obtain a polyacrylonitrile sodium thiocyanate spinning solution. This invention utilizes supercritical carbon dioxide as a medium to dissolve PA in an aqueous sodium thiocyanate solution. Supercritical carbon dioxide has plasticizing and swelling effects. Its swelling effect weakens the effect of strongly polar cyano functional groups and simultaneously reduces the entanglement of PA macromolecular chains, thereby increasing the solubility of PA in the sodium thiocyanate solution and thus increasing the solid content of the spinning solution. The stepwise addition of the sodium thiocyanate solution—first dispersing PA in the first aqueous sodium thiocyanate solution to obtain a dispersion slurry, then adding the second aqueous sodium thiocyanate solution and mixing in a supercritical state—further improves the solubility of PA in the sodium thiocyanate solution.

[0033] According to a preferred embodiment of the present invention, the mass of the second sodium thiocyanate aqueous solution is 10-15 wt% higher than the mass content of the first sodium thiocyanate aqueous solution.

[0034] According to a preferred embodiment of the present invention, the mass content of the first sodium thiocyanate aqueous solution is 35-45 wt%, preferably 41-45 wt%, which is beneficial to improving the solubility of polyacrylonitrile in sodium thiocyanate solution.

[0035] According to a preferred embodiment of the present invention, the mass ratio of polyacrylonitrile to the first sodium thiocyanate aqueous solution is 1:1-10, preferably 1:2.5-5; this is beneficial to improving the solubility of polyacrylonitrile in the sodium thiocyanate solution.

[0036] According to a preferred embodiment of the present invention, the mass ratio of the dispersion slurry to the second sodium thiocyanate aqueous solution is 1:0.3-2, preferably 1:0.5-1.5, such that the mass content of sodium thiocyanate in the polyacrylonitrile spinning solution is 40-45 wt% and the mass content of polyacrylonitrile is 14-16 wt%.

[0037] According to a preferred embodiment of the present invention, the mass content of the second sodium thiocyanate aqueous solution is 45-66 wt%, preferably 50-61 wt%, which is beneficial to improving the solubility of polyacrylonitrile in sodium thiocyanate solution.

[0038] According to a preferred embodiment of the present invention, the polyacrylonitrile has a number-average molecular weight of 20,000-100,000, preferably 20,000-80,000. The present invention does not particularly limit the morphology of the polyacrylonitrile; for the present invention, the polyacrylonitrile is in powder form. The aforementioned polyacrylonitrile is beneficial for improving the solubility of polyacrylonitrile in sodium thiocyanate solution.

[0039] According to the present invention, after the dispersed slurry is discharged into a CO2 atmosphere, the CO2 is heated and pressurized to bring it to a supercritical state for mixing. The temperature and pressure are adjusted to maintain the CO2 in a supercritical state. Preferably, the supercritical temperature of CO2 is 50-90°C, more preferably 60-90°C. The aforementioned supercritical state is beneficial for improving the solubility of polyacrylonitrile in sodium thiocyanate solution.

[0040] According to the present invention, CO2 can be brought into a supercritical state by adjusting the temperature and pressure. Preferably, the supercritical pressure of CO2 is 8-18 MPa, more preferably 8-16 MPa. The aforementioned supercritical state is beneficial for improving the solubility of polyacrylonitrile in sodium thiocyanate solution.

[0041] According to the present invention, supercritical carbon dioxide is used as a medium to dissolve polyacrylonitrile in an aqueous solution of sodium thiocyanate for a mixing time of 2-15 min.

[0042] According to the present invention, mixing is carried out under stirring conditions, preferably at a stirring speed of 10-800 r / min for 2-15 min.

[0043] According to the present invention, after mixing, the solution is cooled and depressurized to obtain a sodium polyacrylonitrile thiocyanate spinning solution, preferably cooled to 25-30°C.

[0044] According to the present invention, after mixing, the solution is cooled and depressurized to obtain a sodium polyacrylonitrile thiocyanate spinning solution. Preferably, the depressurization time is 2-6 minutes.

[0045] According to the present invention, a filtration device with a pore size of 0.5-5 μm is preferably used to filter the polyacrylonitrile sodium thiocyanate spinning solution obtained after cooling and depressurization, so as to remove gel particles in the polyacrylonitrile sodium thiocyanate spinning solution that affect spinning; preferably, the filtration device is selected from at least one of filter screen, filter cloth and sintered metal mesh.

[0046] According to a preferred embodiment of the present invention, the preparation method of the polyacrylonitrile sodium thiocyanate spinning solution is carried out in a supercritical mixing reactor and includes the following steps:

[0047] (1) Add polyacrylonitrile (PAN) powder to a sodium thiocyanate aqueous solution to obtain a dispersion slurry. Place the dispersion slurry in a supercritical mixing vessel, remove the air from the mixing vessel, and make the mixing vessel be in a CO2 atmosphere.

[0048] (2) Add sodium thiocyanate aqueous solution to the supercritical mixing vessel, heat and pressurize to make CO2 in a supercritical state, stir and mix for a certain time, cool down, depressurize and take out the spinning solution in the supercritical mixing vessel, and filter the spinning solution through a filter screen with a pore size of 0.5-5μm to obtain polyacrylonitrile sodium thiocyanate spinning solution.

[0049] According to the present invention, CO2 can be repeatedly introduced to expel air, so that the mixing vessel is in a CO2 atmosphere, for example, CO2 can be introduced to expel air 2-6 times.

[0050] According to the present invention, the mixing vessel can be evacuated and filled with carbon dioxide once or multiple times to remove the air, for example, evacuated and filled with carbon dioxide 2-4 times to remove the air, so that the mixing vessel is in a CO2 atmosphere.

[0051] According to the present invention, the pressurization can be achieved by introducing carbon dioxide into the supercritical mixing vessel to bring CO2 into a supercritical state.

[0052] According to a third aspect of the present invention, the present invention provides the application of the sodium thiocyanate spinning solution of polyacrylonitrile described herein in the preparation of polyacrylonitrile fibers.

[0053] According to a fourth aspect of the present invention, a method of spinning is provided, the method comprising:

[0054] (1) Prepare a polyacrylonitrile sodium thiocyanate spinning solution according to the method of the present invention;

[0055] (2) The polyacrylonitrile spinning solution prepared in step (1) is subjected to spinning and hot stretching treatment to obtain polyacrylonitrile precursor fiber.

[0056] According to the present invention, there are no special requirements for the spinning method. Preferably, in step (2), the spinning method is wet spinning or dry-jet wet spinning.

[0057] According to the present invention, there are no special requirements for the stretching method, but the stretching method is preferably hot stretching, preferably hot water stretching, hot steam stretching or high pressure steam stretching; more preferably the stretching ratio is 2-50 times.

[0058] This invention provides a polyacrylonitrile precursor fiber, which undergoes N tests to determine the axial micropore size, yielding an average value L = (l1 + l2 + l3 + l4 + l5 + l... + l N )*r / N, where r is the radius of the polyacrylonitrile fiber, l N The axial micropore size value of the Nth test; the variance S of the L values ​​of the n polyacrylonitrile precursor fibers. 2 , of which S 2 ≤120, where N is an integer not less than 2 and n is an integer not less than 2. The polyacrylonitrile precursor fiber of the present invention has excellent stability.

[0059] According to one embodiment of the present invention, five samples are tested for each batch of fibers, and the axial micropore size of each sample is tested five times. The average axial micropore size L is calculated, and then the variance S of the five L values ​​(L1, L2, L3, L4, L5) is calculated. 2 ,in,

[0060] According to a preferred embodiment of the present invention, the tensile strength of the polyacrylonitrile precursor filament is preferably 5.5-9 cN / dtex, and more preferably 5.81-8.94 cN / dtex.

[0061] According to a preferred embodiment of the present invention, the tensile modulus of the polyacrylonitrile precursor filament is preferably 95-120 cN / dtex, and more preferably 97.83-116.02 cN / dtex.

[0062] According to a preferred embodiment of the present invention, the axial micropore size inside the polyacrylonitrile precursor fiber for synchrotron small-angle X-ray scattering testing is preferably 80-1200 nm, and more preferably 80-300 nm.

[0063] According to a preferred embodiment of the present invention, the micropore deviation angle of the polyacrylonitrile precursor monofilament is preferably 10°-30°, and more preferably 10°-25°.

[0064] According to a preferred embodiment of the present invention, the fiber orientation factor of the polyacrylonitrile precursor monofilament is preferably 0.915-0.989, more preferably 0.943-0.989.

[0065] According to a preferred embodiment of the present invention, the orientation angle of the microcrystals on the (100) crystal plane of the polyacrylonitrile precursor filament is preferably 5°-13°, and more preferably 5°-9°.

[0066] The polyacrylonitrile precursor fiber of this invention has good stability, and its various physicochemical properties can reach the leading level in the industry, which has strong industrial value.

[0067] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0068] In this invention, the solid content of the polyacrylonitrile sodium thiocyanate spinning solution refers to the mass content of polyacrylonitrile in the polyacrylonitrile sodium thiocyanate spinning solution.

[0069] Swelling reflects the porosity and density of nascent fibers. The test method is as follows: Take a certain mass of nascent fibers, wash them in flowing deionized water for 30 minutes, then dehydrate them in a centrifuge for 15 minutes to remove water adhering to the surface of the solidified filaments and water trapped between the monofilaments; weigh this mass as W. Then dry them in a hot air drying oven at 110℃, and finally cool them to room temperature in a desiccator; weigh this mass as W0. Calculate the swelling degree B using the following formula. G :

[0070] B G = (W-W0) / W0×100

[0071] Used to characterize the percentage of water contained in the pores of 100 parts by weight of nascent filaments.

[0072] The sound velocity value is used to reflect the orientation degree of the nascent fibers. The test is conducted using the MC68VZ328 digital fiber orientation instrument.

[0073] Boiling water shrinkage rate reflects the orientation degree of the amorphous region of the fiber. The test follows the "Test Method for Heat Shrinkage Rate of Synthetic Fiber Filaments" (GB / 6505-2001). Fiber samples of a certain length (L0) are selected and boiled in water at 100℃ for 30 minutes. They are then removed and dried at a temperature range of 50–60℃. After drying, the fiber length L1 is measured again. The boiling water shrinkage rate of the sample is then calculated using the following formula:

[0074] R a = [(L0–L1) / L0]×100%

[0075] In the following examples, 5 samples were tested for each batch of polyacrylonitrile precursor fibers. The axial micropore size of each polyacrylonitrile precursor fiber sample was tested N times, and the average value of the axial micropore size was obtained as L = (l1 + l2 + l3 + l4 + l5 + l... + l N )*r / N, where r is the radius of the polyacrylonitrile fiber, l N The axial micropore size value for the Nth test;

[0076] In the following examples, the axial micropore size of each polyacrylonitrile precursor fiber sample was tested 5 times, and the average axial micropore size L was calculated.

[0077] The average axial micropore size L was measured in five polyacrylonitrile precursor fiber samples.

[0078] The variance S of the five L values ​​(L1, L2, L3, L4, L5) was calculated. 2 ,in,

[0079] In the following embodiments, tensile strength and tensile modulus tests were performed using an XQ-2 tensile testing instrument to record the stress-strain curves of a single fiber. The gauge length of this instrument was 20 mm, and the tensile rate was 20 mm·min. -1 At least 30 valid data points were obtained from each sample, and the average tensile strength and tensile modulus of the PAN fibers were calculated.

[0080] In the following embodiments, the micropore deviation angle and orientation factor were analyzed and tested using small-angle X-ray scattering (SAXS) at the Shanghai Synchrotron Radiation Facility (SSRF) with a wavelength of 0.124 nm (BL14B) and an exposure time of 20 s. During the test, a bundle of PAN fibers was neatly arranged on a sample holder, with the fiber direction perpendicular to the X-ray beam. The distance between the sample and the detector (Mar 345) was calibrated using the standard sample LaB6, and the distance between the fiber and the detector (Mar 345) was 1980 mm. The micropore deviation angle and orientation factor data were analyzed using X-polar software (Precision Works NY, Inc., USA).

[0081] Example 1

[0082] (1) Weigh 140g of PAN powder with a number average molecular weight of 50,000, add 460g of sodium thiocyanate aqueous solution with a concentration of 45%, stir evenly to form a dispersion slurry, place the dispersion slurry in a supercritical mixing vessel, evacuate and fill with carbon dioxide three times to remove the air in the mixing vessel, and keep the mixing vessel in a carbon dioxide atmosphere.

[0083] (2) Add 400g of sodium dithiocyanate aqueous solution with a concentration of 58.25% to the supercritical mixing vessel. When the temperature is raised to 80℃, CO2 is then introduced into the mixing vessel until the pressure is 8MPa, forming a supercritical state in the mixing vessel. The stirring rate is set to 500r / min. After mixing for 8min, the pressure is slowly released for 2min. The spinning solution in the supercritical mixing vessel is then removed. The spinning solution is filtered through a filter screen with a pore diameter of 1μm to obtain a polyacrylonitrile sodium thiocyanate spinning solution. The solid content of the polyacrylonitrile sodium thiocyanate spinning solution is 13.962%.

[0084] (3) The spinning solution obtained in step (2) is spun using wet spinning. The fiber is then thermally stretched using hot water stretching method. The stretching medium is water at 93°C and the stretching ratio is 10 to obtain PAN precursor fiber.

[0085] Sampling and testing of nascent fibers revealed a swelling degree of 157%, a sound velocity of 2023%, and a boiling water shrinkage rate of 12.59%.

[0086] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 6.32 cN / dtex and the modulus was 104.81 cN / dtex. The average axial micropore size in the fiber was 325 nm and the micropore deviation angle was 21.27°. The fiber orientation factor was 0.957. The microcrystal orientation angle of the (100) crystal plane was 8.05° by X-ray diffraction test.

[0087] Example 2

[0088] (1) Weigh 150g of PAN powder with a number average molecular weight of 50,000, add 450g of sodium thiocyanate aqueous solution with a concentration of 45%, stir evenly to form a dispersion slurry, place the dispersion slurry in a supercritical mixing vessel, evacuate and fill with carbon dioxide three times to remove the air in the supercritical mixing vessel, and keep the mixing vessel in a carbon dioxide atmosphere.

[0089] (2) Add 400g of sodium dithiocyanate aqueous solution with a concentration of 59.375% to the supercritical mixing vessel. When the temperature is raised to 80℃, CO2 is introduced into the mixing vessel until the pressure is 8MPa, forming a supercritical state in the mixing vessel. The stirring rate is set to 500r / min. After mixing for 8min, the pressure is slowly released for 2min. The spinning solution in the supercritical mixing vessel is taken out and filtered through a filter screen with a pore diameter of 1μm to obtain a polyacrylonitrile sodium thiocyanate spinning solution. The solid content of the polyacrylonitrile sodium thiocyanate spinning solution is 14.949%.

[0090] (3) The spinning solution obtained in step (2) is spun using wet spinning. The fiber is then thermally stretched using hot water stretching method. The stretching medium is water at 93°C and the stretching ratio is 10 to obtain PAN precursor fiber.

[0091] The nascent fiber samples were tested and found to have a swelling degree of 129%, a sound velocity of 2351%, and a boiling water shrinkage rate of 10.95%.

[0092] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 6.87 cN / dtex and the modulus was 109.25 cN / dtex. The average axial micropore size in the fiber was 239 nm and the micropore deviation angle was 16.73°. The fiber orientation factor was 0.969. The microcrystal orientation angle of the (100) crystal plane was 6.98° by X-ray diffraction test.

[0093] Example 3

[0094] (1) Weigh 160g of PAN powder with a number average molecular weight of 50,000, add 440g of sodium thiocyanate aqueous solution with a concentration of 45%, stir evenly to form a dispersion slurry, place the dispersion slurry in a supercritical mixing vessel, vacuum-fill carbon dioxide three times to remove the air in the mixing vessel, and keep the mixing vessel in a carbon dioxide atmosphere.

[0095] (2) Add 400g of a 60.5% sodium dithiocyanate aqueous solution to a supercritical mixing vessel, heat to 80℃, and then introduce CO2 into the mixing vessel until the pressure reaches 8MPa, forming a supercritical state in the mixing vessel; set the stirring rate to 500r / min, mix for 8min, and then slowly depressurize for 2min, and take out the spinning solution from the supercritical mixing vessel; filter the spinning solution through a filter screen with a pore diameter of 1μm to obtain a polyacrylonitrile sodium thiocyanate spinning solution, the solid content of which is 15.942%.

[0096] (3) The spinning solution obtained in step (2) is spun using wet spinning. The fiber is then thermally stretched using hot water stretching method. The stretching medium is water at 93°C and the stretching ratio is 10 to obtain PAN precursor fiber.

[0097] The nascent fibers were sampled and tested. The swelling degree of the nascent fibers was 112%, the sound velocity of the nascent fibers was 2562%, and the boiling water shrinkage rate of the nascent fibers was 9.96%.

[0098] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 7.29 cN / dtex and the modulus was 113.26 cN / dtex. The average axial micropore size in the fiber was 115 nm and the micropore deviation angle was 11.63°. The fiber orientation factor was 0.977. The microcrystal orientation angle of the (100) crystal plane was 6.03° by X-ray diffraction test.

[0099] Example 4

[0100] (1) Weigh 160g of PAN powder with a number average molecular weight of 50,000, add 440g of sodium thiocyanate aqueous solution with a concentration of 45%, stir evenly to form a dispersion slurry, place the dispersion slurry in a supercritical mixing vessel, evacuate and fill with carbon dioxide four times to remove the air in the mixing vessel, and keep the supercritical mixing vessel in a carbon dioxide atmosphere.

[0101] (2) Add 400g of a 60.5% sodium dithiocyanate aqueous solution to a supercritical mixing vessel. When the temperature is raised to 80℃, CO2 is introduced into the mixing vessel until the pressure is 8MPa, forming a supercritical state in the mixing vessel. The stirring rate is set to 500r / min. After mixing for 8min, the pressure is slowly released for 2min. The spinning solution in the supercritical mixing vessel is then removed. The spinning solution is filtered through a filter screen with a pore diameter of 4μm to obtain a polyacrylonitrile sodium thiocyanate spinning solution with a solid content of 15.989%.

[0102] (3) The spinning solution obtained in step (2) is spun using wet spinning. The fiber is then thermally stretched using hot water stretching method. The stretching medium is water at 93°C and the stretching ratio is 10 to obtain PAN precursor fiber.

[0103] Samples of nascent fibers were tested and found to have a swelling degree of 92%, a sound velocity of 2759%, and a boiling water shrinkage rate of 9.21%.

[0104] The mechanical properties of PAN precursor fibers were tested by measuring the strength of the fiber monofilaments. The tensile strength of the PAN precursor fibers was 7.53 cN / dtex, and the modulus was 115.89 cN / dtex.

[0105] Synchrotron radiation small-angle X-ray scattering test showed that the average axial micropore size inside the fiber was 89 nm, the micropore deviation angle was 10.47°, the fiber orientation factor was 0.987, and the X-ray diffraction test showed that the microcrystal orientation angle of the (100) crystal plane was 5.29°.

[0106] Example 5

[0107] (1) Weigh 160g of PAN powder with a number average molecular weight of 50,000, add 440g of sodium thiocyanate aqueous solution with a concentration of 45%, stir evenly to form a dispersion slurry, place the dispersion slurry in a supercritical mixing vessel, evacuate and fill with carbon dioxide three times to remove the air in the mixing vessel, and keep the mixing vessel in a carbon dioxide atmosphere.

[0108] (2) Add 400g of a 60.5% sodium dithiocyanate aqueous solution to a supercritical mixing vessel. Heat the mixture to 80℃ and then introduce CO2 into the mixing vessel until the pressure reaches 8MPa, thus forming a supercritical state within the mixing vessel. Set the stirring rate to 100r / min and mix for 15min. Then, slowly depressurize for 2min and remove the spinning solution from the supercritical mixing vessel. Filter the spinning solution through a 4μm pore diameter filter to obtain a polyacrylonitrile sodium thiocyanate spinning solution with a solid content of 15.992%.

[0109] (3) The spinning solution obtained in step (2) is spun using wet spinning. The fiber is then thermally stretched using hot water stretching method. The stretching medium is water at 93°C and the stretching ratio is 10 to obtain PAN precursor fiber.

[0110] Samples of nascent fibers were tested and found to have a swelling degree of 91%, a sound velocity of 2772%, and a boiling water shrinkage rate of 9.13%.

[0111] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 7.59 cN / dtex and the modulus was 116.02 cN / dtex. The average axial micropore size in the fiber was 86 nm and the micropore deviation angle was 10.35°. The fiber orientation factor was 0.987. The microcrystal orientation angle of the (100) crystal plane was 5.13° by X-ray diffraction test.

[0112] Example 6

[0113] (1) Weigh 160g of PAN powder with a number average molecular weight of 50,000, add 440g of sodium thiocyanate aqueous solution with a concentration of 45%, stir evenly to form a dispersion slurry, place the dispersion slurry in a supercritical mixing vessel, evacuate and fill with carbon dioxide four times to remove the air in the mixing vessel.

[0114] (2) Add 400g of a 60.5% sodium dithiocyanate aqueous solution to a supercritical mixing vessel. Heat the mixture to 80℃ and then introduce CO2 into the mixing vessel until the pressure reaches 8MPa, thus forming a supercritical state within the mixing vessel. Set the stirring rate to 100r / min, mix for 2 minutes, and then slowly depressurize for 2 minutes. Remove the spinning solution from the supercritical mixing vessel. Filter the spinning solution through a 4μm pore diameter filter to obtain a polyacrylonitrile sodium dithiocyanate spinning solution with a solid content of 15.961%.

[0115] (3) The spinning solution obtained in step (2) is spun using wet spinning. The fiber is then thermally stretched using hot water stretching method. The stretching medium is water at 93°C and the stretching ratio is 10 to obtain PAN precursor fiber.

[0116] Sampling and testing of nascent fibers revealed a swelling degree of 105%, a sound velocity of 2659%, and a boiling water shrinkage rate of 9.71%.

[0117] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 7.33 cN / dtex and the modulus was 114.04 cN / dtex. The average axial micropore size in the fiber was 108 nm and the micropore deviation angle was 11.32°. The fiber orientation factor was 0.980. The microcrystal orientation angle of the (100) crystal plane was 5.77° by X-ray diffraction test.

[0118] Example 7

[0119] The method of Example 6 is different in that, in step (2), 400g of sodium dithiocyanate aqueous solution with a concentration of 60.5% is added to the supercritical mixing vessel, and CO2 is introduced into the mixing vessel to a pressure of 12MPa when the temperature is raised to 90°C. The other conditions are the same as in Example 10.

[0120] The solid content of the polyacrylonitrile sodium thiocyanate spinning solution is 15.975%.

[0121] Samples of nascent fibers were tested and found to have a swelling degree of 98%, a sound velocity of 2720%, and a boiling water shrinkage rate of 9.44%.

[0122] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 7.40 cN / dtex and the modulus was 114.32 cN / dtex. The average axial micropore size in the fiber was 101 nm and the micropore deviation angle was 10.89°. The fiber orientation factor was 0.982. The microcrystal orientation angle of the (100) crystal plane was 5.50° by X-ray diffraction test.

[0123] Example 8

[0124] The method of Example 6 is different in that, in step (2), 400g of sodium dithiocyanate aqueous solution with a concentration of 60.5% is added to the supercritical mixing vessel, and CO2 is introduced into the mixing vessel to a pressure of 12MPa when the temperature is raised to 60°C. The other conditions are the same as in Example 10.

[0125] The solid content of the polyacrylonitrile sodium thiocyanate spinning solution is 15.968%.

[0126] The nascent fiber samples were tested and found to have a swelling degree of 102%, a sound velocity of 2689%, and a boiling water shrinkage rate of 9.60%.

[0127] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 7.32 cN / dtex and the modulus was 114.22 cN / dtex. The average axial micropore size in the fiber was 105 nm and the micropore deviation angle was 11.09°. The fiber orientation factor was 0.981. The microcrystal orientation angle of the (100) crystal plane was 5.70° by X-ray diffraction test.

[0128] Example 9

[0129] The method of Example 6 is different in that, in step (2), 400g of sodium dithiocyanate aqueous solution with a concentration of 60.5% is added to the supercritical mixing vessel, and CO2 is introduced into the mixing vessel to a pressure of 12MPa when the temperature is raised to 50°C. The other conditions are the same as in Example 10.

[0130] The solid content of the polyacrylonitrile sodium thiocyanate spinning solution is 15.959%.

[0131] The nascent fiber samples were tested and found to have a swelling degree of 109%, a sound velocity of 2603%, and a boiling water shrinkage rate of 9.78%.

[0132] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 7.30 cN / dtex and the modulus was 113.89 cN / dtex. The average axial micropore size in the fiber was 111 nm and the micropore deviation angle was 11.37°. The fiber orientation factor was 0.979. The microcrystal orientation angle of the (100) crystal plane was 5.81° by X-ray diffraction test.

[0133] Example 10

[0134] The method of Example 6 is the same as in Example 10, except that in step (1), the number average molecular weight of the PAN powder is 20,000.

[0135] The solid content of the polyacrylonitrile sodium thiocyanate spinning solution is 15.968%.

[0136] Samples of nascent fibers were tested and found to have a swelling degree of 104%, a sound velocity of 2669%, and a boiling water shrinkage rate of 9.68%.

[0137] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 7.30 cN / dtex and the modulus was 113.72 cN / dtex. The average axial micropore size in the fiber was 111 nm and the micropore deviation angle was 11.74°. The fiber orientation factor was 0.976. The microcrystal orientation angle of the (100) crystal plane was 5.82° by X-ray diffraction test.

[0138] Example 11

[0139] Compared with Example 6, the difference is that in step (1), the amount of the first sodium thiocyanate aqueous solution added is 320g; in step (2), the concentration of the second sodium thiocyanate aqueous solution is 56.92%, and the amount added is 520g; the conditions are the same as in Example 10.

[0140] The solid content of the polyacrylonitrile sodium thiocyanate spinning solution is 15.012%.

[0141] Samples of nascent fibers were tested and found to have a swelling degree of 121%, a sound velocity of 2409%, and a boiling water shrinkage rate of 10.81%.

[0142] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 6.96 cN / dtex and the modulus was 110.04 cN / dtex. The average axial micropore size in the fiber was 208 nm and the micropore deviation angle was 16.22°. The fiber orientation factor was 0.972. The microcrystal orientation angle of the (100) crystal plane was 6.91° by X-ray diffraction test.

[0143] Example 12

[0144] Compared with Example 6, the difference is that in step (1), the concentration of the first sodium thiocyanate aqueous solution is 40 wt%; in step (2), the concentration of the second sodium thiocyanate aqueous solution is 66 wt%, and the other conditions are the same as in Example 10.

[0145] The solid content of the polyacrylonitrile sodium thiocyanate spinning solution is 14.893%.

[0146] The nascent fibers were sampled and tested. The swelling degree of the nascent fibers was 130%, the sound velocity of the nascent fibers was 2339%, and the boiling water shrinkage rate of the nascent fibers was 11.01%.

[0147] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 6.81 cN / dtex and the modulus was 109.04 cN / dtex. The average axial micropore size in the fiber was 256 nm and the micropore deviation angle was 16.82°. The fiber orientation factor was 0.961. The microcrystal orientation angle of the (100) crystal plane was 7.05° by X-ray diffraction test.

[0148] Comparative Example 1

[0149] Compared with Example 1, the difference is that in step (2), the carbon dioxide introduced into the mixing vessel is replaced with air, and the other conditions are the same as in Example 1.

[0150] The solid content of the polyacrylonitrile sodium thiocyanate spinning solution is 11.013%.

[0151] The nascent fibers were sampled and tested, and the swelling degree of the nascent fibers was measured to be 261%, the sound velocity value of the nascent fibers was 892%, and the boiling water shrinkage rate of the nascent fibers was 20.82%.

[0152] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 4.59 cN / dtex and the modulus was 93.19 cN / dtex. The average axial micropore size in the fiber was 973 nm and the micropore deviation angle was 39.93°. The fiber orientation factor was 0.894. The microcrystal orientation angle of the (100) crystal plane was 13.78° by X-ray diffraction test.

[0153] Comparative Example 2

[0154] (1) Weigh 140g of PAN powder with a molecular weight of 50,000, add 460g of sodium thiocyanate aqueous solution with a concentration of 45%, stir evenly to form a dispersion slurry, and place the dispersion slurry in a glass beaker.

[0155] (2) Add 400g of sodium dithiocyanate aqueous solution with a concentration of 58.25% to a glass beaker and heat it to 80℃. Set the stirring rate to 800r / min and mix for 8min. Take out the spinning solution and filter it through a filter screen with a pore diameter of 1μm to obtain a polyacrylonitrile sodium thiocyanate spinning solution with a solid content of 10.973%.

[0156] (3) The spinning solution obtained in step (2) is spun using wet spinning. The fiber is then thermally stretched using hot water stretching method. The stretching medium is water at 93°C and the stretching ratio is 10 to obtain PAN precursor fiber.

[0157] The nascent fibers were sampled and tested. The swelling degree of the nascent fibers was 272%, the sound velocity of the nascent fibers was 783%, and the boiling water shrinkage rate of the nascent fibers was 21.22%.

[0158] The mechanical properties of PAN precursor fiber were tested by fiber monofilament strength test. The tensile strength of PAN precursor fiber was 4.52 cN / dtex and the modulus was 93.01 cN / dtex. The average internal axial micropore size of the fiber was 1034 nm and the micropore deviation angle was 41.22°. The fiber orientation factor was 0.879. The microcrystal orientation angle of the (100) crystal plane was 14.45° by X-ray diffraction test.

[0159] Table 1

[0160]

[0161] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A polyacrylonitrile sodium thiocyanate spinning solution, characterized in that, The polyacrylonitrile content in the sodium polyacrylonitrile thiocyanate spinning solution is 14-16 wt% by mass fraction, and the sodium polyacrylonitrile thiocyanate spinning solution contains 40 wt%-45 wt% sodium thiocyanate. The preparation method of the polyacrylonitrile sodium thiocyanate spinning solution includes: dispersing polyacrylonitrile in a first sodium thiocyanate aqueous solution to obtain a dispersion slurry; placing the dispersion slurry in a carbon dioxide atmosphere; adding a second sodium thiocyanate aqueous solution under a carbon dioxide atmosphere, then introducing CO2 under pressure and heating to bring the CO2 to a supercritical state for mixing; after mixing, cooling and depressurizing to obtain the polyacrylonitrile sodium thiocyanate spinning solution; the supercritical CO2 temperature is 60-90℃, the supercritical CO2 pressure is 8-16MPa, and the mixing time is 2-15min; the mass content of the second sodium thiocyanate aqueous solution is 10wt%-15wt% higher than the mass content of the first sodium thiocyanate aqueous solution. The polyacrylonitrile has a number-average molecular weight of 20,000 to 100,000. The mass ratio of polyacrylonitrile to sodium thiocyanate aqueous solution is 1:1-10; The mass ratio of the dispersed slurry to the sodium dithiocyanate aqueous solution is 1:0.3-2.

2. The polyacrylonitrile sodium thiocyanate spinning solution according to claim 1, wherein, The polyacrylonitrile sodium thiocyanate spinning solution contains 40wt%-45wt% sodium thiocyanate, 14wt%-16wt% polyacrylonitrile and 39wt%-54wt% water.

3. The polyacrylonitrile sodium thiocyanate spinning solution according to claim 2, wherein, The polyacrylonitrile has a number-average molecular weight of 20,000 to 80,000.

4. The polyacrylonitrile sodium thiocyanate spinning solution according to claim 1, wherein, The first sodium thiocyanate aqueous solution has a mass content of 35-45 wt%; and / or The second sodium thiocyanate aqueous solution has a mass content of 45-66 wt%.

5. The polyacrylonitrile sodium thiocyanate spinning solution according to claim 1, wherein, The first sodium thiocyanate aqueous solution has a mass content of 41-45 wt%; and / or The mass ratio of polyacrylonitrile to sodium thiocyanate aqueous solution is 1:2.5-5; and / or The mass ratio of the dispersed slurry to the sodium dithiocyanate aqueous solution is 1:0.5-1.5; and / or The second sodium thiocyanate aqueous solution has a mass content of 50~61wt%.

6. The polyacrylonitrile sodium thiocyanate spinning solution according to claim 1, wherein, Cool down to 25-30℃; and / or the pressure relief time is 2-6 min; and / or The cooled and depressurized sodium polyacrylonitrile thiocyanate spinning solution was filtered using a filter material with a pore size of 0.5-5 μm.

7. The polyacrylonitrile sodium thiocyanate spinning solution according to claim 6, wherein, Mix at a stirring speed of 10-800 r / min for 2-15 min; and / or The filter material is selected from at least one of filter screens, filter cloths, and sintered metal meshes.

8. The application of the polyacrylonitrile sodium thiocyanate spinning solution according to claims 1-7 in the preparation of polyacrylonitrile fibers.

9. A spinning method, characterized in that, The method includes: The polyacrylonitrile sodium thiocyanate spinning solution described in claims 1-7 is subjected to spinning and hot stretching treatment to obtain polyacrylonitrile precursor fibers.

10. The spinning method according to claim 9, wherein, The spinning method is wet spinning or dry-jet wet spinning; and / or The draw ratio is 2-50 times.

11. The spinning method according to claim 10, wherein, The hot stretching process can be hot water stretching, hot steam stretching, or high-pressure steam stretching.

12. A polyacrylonitrile precursor fiber, characterized in that, The axial micropore size of the polyacrylonitrile precursor fiber was tested N times, and the average value of the axial micropore size was obtained as L = (l1 + l2 + l3 + l4 + l5 + ... + l N ) r / N, where r is the radius of the polyacrylonitrile fiber, l N The axial micropore size value of the Nth test; the variance S of the L values ​​of the n polyacrylonitrile precursor fibers. 2 , of which S 2 ≤120, where N is an integer not less than 2 and n is an integer not less than 2.

13. The polyacrylonitrile precursor fiber according to claim 12, wherein, The tensile strength of this polyacrylonitrile precursor monofilament is 5.5-9 cN / dtex; and / or The tensile modulus of the polyacrylonitrile precursor monofilament is 95-120 cN / dtex; and / or Synchrotron radiation small-angle X-ray scattering (SAXS) analysis of the polyacrylonitrile precursor monofilament showed that the axial micropore size within the fiber was 80-1200 nm; and / or The micropore deviation angle of the polyacrylonitrile precursor monofilament is 10°. o -30 o ; and / or The fiber orientation factor of the polyacrylonitrile precursor monofilament is 0.915-0.989; and / or X-ray diffraction analysis of the polyacrylonitrile precursor filament showed that the orientation angle of the microcrystals on the (100) crystal plane was 5°. o -13 o .

14. The polyacrylonitrile precursor fiber according to claim 12 or 13, wherein, The tensile strength of the polyacrylonitrile precursor monofilament is 5.81-8.94 cN / dtex; and / or The tensile modulus of the polyacrylonitrile precursor monofilament is 97.83-116.02 cN / dtex; and / or Synchrotron radiation small-angle X-ray scattering (SAXS) analysis of the polyacrylonitrile precursor monofilament showed that the axial micropore size within the fiber was 80-300 nm; and / or The micropore deviation angle of the polyacrylonitrile precursor monofilament is 10°. o -25 o ; and / or The fiber orientation factor of the polyacrylonitrile precursor monofilament is 0.943-0.989; and / or X-ray diffraction analysis of the polyacrylonitrile precursor filament showed that the orientation angle of the microcrystals on the (100) crystal plane was 5°. o -9 o .

Citation Information

Patent Citations

  • Polyacrylonitrile suspension with high solid content and low viscosity, preparation method and application thereof, and preparation method of polyacrylonitrile-based carbon fiber

    CN113072658A

  • Preparation method for polyacrylonitrile-based carbon fiber protofilament

    CN102953139A

  • Preparation method of low-cost polyacrylonitrile-based carbon fiber

    CN107653520A